FACTORS IMPACTING THE REFERRAL TIME TO NEPHROLOGISTS IN CHRONIC KIDNEY DISEASE PATIENTS IN SOUTH PUNJAB, PAKISTAN - KHALID, P; SAEED, AA; JAUHAR, M; AHMED, R; ABBAS, G (Biological and Clinical Sciences Research Journal, 2022)
To assess the social, demographic, clinical and health factors impacting the referral time to a nephrologist in chronic kidney disease patients. A prospective study was carried out at Nephrology Department of Nishtar Medical Hospital, Multan from October 2021-October 2022. A total of 150 chronic kidney disease patients who were undergoing dialysis were selected for the study. Early and late referral time was evaluated by the time period between referral and dialysis initiation. All the patients were interviewed for evaluation of factors affecting the referral time. The analysis showed that 92 patients (61.3%) were in early referral and 58 patients (38.6%) were in late referral among which 21 patients were referred to a nephrologist almost 90 days prior to the dialysis initiation. Patients in the late referral mostly had diabetes, congestive heart failure or hypertension, whereas patients in early referral were non-smokers, women and patients with glomerulonephritis. The multivariate analysis revealed the following independent risk factors for late referral: kidney disease (diabetes mellitus: OR 1.499, 95% CI 1.049–2.142, hypertension OR 1.989, 95% CI 1.299–3.048), male sex (OR: 1.455, 95% CI: 1.029–2.069), congestive heart failure (OR 2.137, 95% CI 1.537–2.997), profession (labourer OR 3.199, 95% CI 1.398–7.320, mechanic OR 2.969, 95% CI 1.439–6.119, farmer OR 5.139, 95% CI 2.210–11.938) and assisted walks (OR 2.066, 95% CI 1.377–3.107). Diabetes and hypertension patients have a later referral time than patients with glomerulonephritis. In addition, men with congestive heart failure practicing physically active professions and assisted ambulation were referred late.